Correlation between Electrical Conductivity and Total Dissolved Solids in Natural Waters - Thirumalini, S.; Joseph, Kurian (Malaysian Journal of Science, 2009)
The study aims at establishing the correlation ratio between Total Dissolved Solids (TDS )and Electrical Conductivity ( EC ) for natural waters such as fresh water , sea water and tender coconut .The EC value can be obtained from in situ conductivity measurements since it is quick reliable and relatively of low cost . Twenty four fresh water , fifteen sea water and twenty eight ( eight from pollution free area and twenty from textile industrial belt) tender coconut samples were considered for the analysis various water quality parameters. In sea water, the result indicates 96 % of the variability in TDS could be ascertained to the variable EC. The regression equation for sea water is in the form of y = bx + c where b is the correlation ratio due to ionic species and the intercept c values are assigned to unionic species. In the case of tender coconut, the correlation ratio was found to be 0.63 for samples taken from pollution free residential areas where as the ratio found to be varied between 0.59 to 0.93 in textile industrial belt.